Інформаційно-комунікаційні платформи бібліотек - Наливайко, Орест (Видавництво Львівської політехніки, 2025)
Libraries actively use social media as a channel of communication with a wide range of users, distributing information about events, resources, and services, but do not sufficiently utilize the potential for interactivity and feedback.
Keywords: цифрова комунікація цифрова трансформація; соціальні медіа; соціальна медіаплатформа; бібліотека